Adaptation and exogenous attention interact in the early visual cortex: A TMS study - Hsing-Hao Lee; Antonio Fernández; Marisa Carrasco (iScience)
Summary: Transcranial magnetic stimulation (TMS) to early visual cortex modulates the effect of adaptation and eliminates the effect of exogenous (involuntary) attention on contrast sensitivity. Here, we investigated whether adaptation modulates exogenous attention under TMS to V1/V2. Observers performed an orientation discrimination task while attending to one of two stimuli, with or without adaptation. Following an attentional cue, two stimuli were presented in the stimulated region and its contralateral symmetric region. A response cue indicated the stimulus whose orientation observers had to discriminate. Without adaptation, in the distractor-stimulated condition, contrast sensitivity increased at the attended location and decreased at the unattended location via response gain—but these effects were eliminated in the target-stimulated condition. Critically, after adaptation, exogenous attention altered performance similarly in both distractor-stimulated and target-stimulated conditions. These results reveal that (1) adaptation and attention interact in the early visual cortex, and (2) adaptation shields exogenous attention from TMS effects.